The Influence of Paternalistic Leadership On Individual Performance - Anhar Januar Malik; C. Budi Santoso (Universitas Gadjah Mada, 2022)
Introduction/Main Objectives: Paternalistic leadership as a unique leadership behavior has received the attention of researchers from various countries. The application of effective paternalistic leadership occurs in high power-distance and collectivistic cultures. Background Problems: Most studies examine the influence of paternalistic leadership at the dimensional level. In addition, the issue in paternalistic leadership research is directed to review the presence of paternalistic leadership on members’ attitudes. Novelty: First, this study is aimed at testing the united dimensions of paternalistic leadership. Second, this study focuses on the psychological mechanisms underlying the impact of paternalistic leadership on individual tasks and contextual performance. Third, this study adopts social exchange theory and affective events theory to review the role of paternalistic leadership. Research Methods: Using a statistical test of mediating process with the approach of the causal chain. This research was carried out in the context of organizations in various sectors. Finding/Results: Firstly, paternalistic leadership is present in varied organizations. Secondly, paternalistic leadership significantly influences individual tasks and contextual performance. Moreover, the findings reveal that trust in leadership enables to explain the relationship between paternalistic leadership and individual tasks and contextual performance.